Impact of tunnel gate process variations on analog/radio frequency (microwave) and small signal parameters of hetero‐material tunneling interfaced charge plasma junctionless tunnel field effect transistor. (9th June 2022) - Sharma, Samriti; Chaujar, Rishu
Abstract: This paper proposes a dual metal gate, hetero‐material tunneling interfaced junctionless tunnel field effect transistor (TFET), (DMG‐HJLTFET), utilizing III–V compound semiconducting materials, InAs (low band‐gap source material)/GaAs (higher band‐gap channel and drain material) by applying the band‐gap and dual material gate engineering. The 2‐D TCAD simulations have been executed to explore the impact of tunnel gate process variations—work function and length on DC and analog figure of merits (FOMs) of DMG‐HJLTFET. The extracted result parameters have also been compared to SMG (single metal gate)‐HJLTFET and conventional Si‐JLTFET. The DMG‐HJLTFET attains improved ON current in the range of 88.5 × 10 −6  A/μm and OFF current remains as low as 2.89 × 10 −16  A/μm. It exhibits a high current switching ratio of 3.1 × 10 11 as compared to SMG‐HJLTFET (ION  = 24 × 10 −6  A/μm and ION /IOFF  = 1.4 × 10 11 ) and Si‐JLTFET (ION  = 7 × 10 −6  A/μm and ION /IOFF  = 1.8 × 10 6 ). Further, the radio frequency/microwave (RF) parameters such as power gains (h12, UPG, and Gma), fmax, and GBP have been compared for all three aforementioned devices. Moreover, the small signal admittance (Y) parameters have been examined to explore the possible scope of DMG‐HJLTFET for future internet of everything communications and fast switching applications. Abstract : This paper proposes a dual metal gate, hetero‐material tunneling interfaced junctionless tunnel field effect transistor (TFET), (DMG‐HJLTFET), utilizing III–V compound semiconducting materials, InAs (low band‐gap source material)/GaAs (higher band‐gap channel and drain material) by applying band‐gap and dual material gate engineering. The 2‐D TCAD simulations have been executed to explore the impact of tunnel gate process variations—work function and length on DC and analog performance of DMG‐HJLTFET. The extracted result parameters have also been compared to single metal gate‐HJLTFET and conventional Si‐JLTFET.